2004
DOI: 10.1007/s00181-003-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Do stock market returns predict changes to output? Evidence from a nonlinear panel data model

Abstract: Recent empirical work suggests a predictive relationship between stock returns and output growth. We employ quarterly data from a panel of 27 countries to test whether stock returns as useful in predicting growth. Unlike previous research, our approach allows for the possible non-linear effect of recessions on the growth-return relationship. There is strong evidence to suggest that a linear model would be misspecified and provide potentially misleading inference. Using a switching regression approach, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Moreover, in this case where z is i.i.d., changes in Q will not forecast output. This matches the finding of Henry et al (2005) that the stock market predicts growth better in recessions than in booms.…”
Section: Lemmasupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, in this case where z is i.i.d., changes in Q will not forecast output. This matches the finding of Henry et al (2005) that the stock market predicts growth better in recessions than in booms.…”
Section: Lemmasupporting
confidence: 79%
“…By Corollary 1, w is concave in s which means that w s is decreasing in s. By Corollary 2, x is increasing in s so that (z − x) σ is decreasing in s. Thus the claim holds for p and, by (21) it also holds for q.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…However, many researchers tend to focus on contagion effect amongst stock markets and ignore the linkages between economic activities and stock market's condition. In fact, both economic activities and stock market's condition play a significant role in determining the direction of portfolio diversification which is especially true during recession (Henry, Ólan, Olekalns & Thong 2004). Moreover, stock markets of countries that are economically integrated tend to respond in similar manners to global economic shocks (Morona, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an empirical work on a sample of 27 countries including G7 2 and Southeast Asian economies, Henry et al (2004) used switching regression analysis to examine the relationship between stock returns and growth rates during the period 1982-2001. The authors concluded that in the Organization for Economic Cooperation and Development (OECD) and in five Southeast Asian countries (Hong Kong, Korea, the Philippines, Singapore, and Taiwan) there was a significant relationship between stock returns and economic growth.…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%